Melatonin Affects the Photosynthetic Performance of Pepper (Capsicum annuum L.) Seedlings under Cold Stress - Muhammad Ahsan Altaf; Huangying Shu; Yuanyuan Hao; Muhammad Ali Mumtaz; Xu Lu; Zhiwei Wang (MDPI AG, 2022)
Photosynthesis is an important plant metabolic mechanism that improves carbon absorption and crop yield. Photosynthetic efficiency is greatly hampered by cold stress (CS). Melatonin (ME) is a new plant growth regulator that regulates a wide range of abiotic stress responses. However, the molecular mechanism of ME-mediated photosynthetic regulation in cold-stressed plants is not well understood. Our findings suggest that under low-temperature stress (15/5 °C for 7 days), spraying the plant with ME (200 µM) enhanced gas exchange characteristics and the photosynthetic pigment content of pepper seedlings, as well as upregulated their biosynthetic gene expression. Melatonin increased the activity of photosynthetic enzymes (Rubisco and fructose-1, 6-bisphosphatase) while also enhancing starch, sucrose, soluble sugar, and glucose content under CS conditions. Low-temperature stress significantly decreased the photochemical activity of photosystem II (PSII) and photosystem I (PSI), specifically their maximum quantum efficiency PSII (Fv/Fm) and PSI (Pm). In contrast, ME treatment improved the photochemical activity of PSII and PSI. Furthermore, CS dramatically reduced the actual PSII efficiency (ΦPSII), electron transport rate (ETR) and photochemical quenching coefficient (qP), while enhancing nonphotochemical quenching (NPQ); however, ME treatment substantially mitigated the effects of CS. Our results clearly show the probable function of ME treatment in mitigating the effects of CS by maintaining photosynthetic performance, which might be beneficial when screening genotypes for CS tolerance.